Unraveling the Molecular Mechanisms Underlying the Nasopharyngeal Bacterial Community Structure - Wouter A. A. de Steenhuijsen Piters (American Society for Microbiology, 2016)
ABSTRACT The upper respiratory tract is colonized by a diverse array of commensal bacteria that harbor potential pathogens, such as Streptococcus pneumoniae. As long as the local microbial ecosystem—also called “microbiome”—is in balance, these potentially pathogenic bacterial residents cause no harm to the host. However, similar to macrobiological ecosystems, when the bacterial community structure gets perturbed, potential pathogens can overtake the niche and cause mild to severe infections. Recent studies using next-generation sequencing show that S. pneumoniae, as well as other potential pathogens, might be kept at bay by certain commensal bacteria, including Corynebacterium and Dolosigranulum spp. Bomar and colleagues are the first to explore a specific biological mechanism contributing to the antagonistic interaction between Corynebacterium accolens and S. pneumoniae in vitro [L. Bomar, S. D. Brugger, B. H. Yost, S. S. Davies, K. P. Lemon, mBio 7(1):e01725-15, 2016, doi:10.1128/mBio.01725-15]. The authors comprehensively show that C. accolens is capable of hydrolyzing host triacylglycerols into free fatty acids, which display antipneumococcal properties, suggesting that these bacteria might contribute to the containment of pneumococcus. This work exemplifies how molecular epidemiological findings can lay the foundation for mechanistic studies to elucidate the host-microbe and microbial interspecies interactions underlying the bacterial community structure. Next, translation of these results to an in vivo setting seems necessary to unveil the magnitude and importance of the observed effect in its natural, polymicrobial setting.